Unlawful Enrichment and Underdevelopment in African Societies in Alobwed 'Epie's The Death Certificate - GBAGUIDI, CELESTIN; HOUNDJO, THÉOPHILE; ADIMI, Dimon Mickael; GBAGUIDI, CELESTIN (My University, 2018)
Abstract: Scores of post-colonial narratives revolve around the detrimental impact of colonisation on the development level of Africa. As opposed to those works which put forth a discourse of white men as the source of the underdevelopment of African countries, a fictional narrative by Alobwed'Epie - The Death Certificate which is a novel of disillusionment- shifts attention from the white and focuses on the practices of Africans themselves which hinder development on the continent. Through the lens of Socio-criticism theory, the objective of this paper is first, to show how tribalism and clannish management weaken the fictional postcolonialstate Ewawa. Second, it points out how weak state institutions offer a favourable ground for African elites who profit from their positions to achieve an unlawful enrichment. To answer the different questions contributing to reach the objectives of this paper, a qualitative research method has been used.
Keywords: Unlawful enrichment - Corruption - The Death Certificate – underdevelopment